Shakespeare's curtain: The stage revealed or the stage re-veiled?. Issue 1 (July 2019) - Grzegorzewska, Małgorzata
This article takes advantage of Jean-Luc Marion's post-phenomenological reflection in order to analyse the different modes of seeing and looking suggested in William Shakespeare's plays. It highlights the difference between the indoor stage, where the audience's attention is focused on the lighted and framed space of the stage, and an open-air performance, which struggles to wrest attention from the spectator's gaze. A theological turn in the argument accounts for the transition from the description of a concealment/discovery space in Elizabethan theatre to what the author defines as the 'space of revelation' recreated in contemporary theatre.